A prospective randomized controlled study of Li quick repositioning maneuver for geotropic horizontal canal BPPV. (2nd September 2018) - Li, Jinrang; Zou, Shizhen; Tian, Shiyu
Abstract: Background: Li quick repositioning maneuver for treatment of geotropic horizontal canal benign paroxysmal positional vertigo (HC-BPPV) was reported in the literature. Objective: The aim of this study is to observe the clinical efficacy of the Li quick repositioning maneuver for the treatment of geotropic HC-BPPV. Methods: The single-blind method was used to conduct a prospective controlled study on 120 patients with geotropic HC-BPPV from May 2014 to May 2017. Patients were randomly assigned to the Li quick repositioning maneuver (Li maneuver) group or the barbecue repositioning maneuver (barbecue maneuver) group. Results: The successful repositioning rates were 53.3%, 70.4%, 90.7% and 92.3%, respectively, in barbecue maneuver group and 61.7%, 80.7%, 93.0% and 96.3%, respectively, in Li maneuver group at 1-day, 3-day, 1-week and 1-month follow-up. Differences in success rates of repositioning between Li and barbecue maneuver groups at 1 day, 3 days, 1 week and 1 month after initial treatment were not statistically significant using the Kaplan–Meier survival curve with a log-rank test ( p = .270) . Conclusion: The Li maneuver is a rapid, simple and efficacious repositioning method for geotropic HC-BPPV and can be widely applied in clinical practice as an alternative method.